Ecocracy and Rights of Nature: Constitutional Reconstruction of Indonesian Energy Transition Mining - Wahyu Nugroho; Muhammad Umar bin Abdul Razak (Siyasah Dusturiyah: State Law Review, 2026)
The global energy transition paradoxically has triggered massive nickel mining operations, severely threatening critical ecological vulnerabilities of small islands in Indonesia. This study aims to reconstruct the conventional anthropocentric Green Constitution paradigm by systematically integrating the Ecocracy doctrine and Rights of Nature. Utilizing a normative-juridical method with conceptual, statutory, and case approaches, this research analyzes various contemporary constitutional shifts. The study findings demonstrate that unregulated nickel extraction fundamentally destroys the ecological carrying capacity of vulnerable archipelagos. Crucially, Constitutional Court Decision Number 35/PUU-XXI/2023 functions as a monumental judicial resolution that firmly and implicitly recognizes nature as an independent legal subject holding absolute protection rights. In conclusion, this historic ruling establishes an erga omnes constitutional mandate for the state to immediately halt all destructive extractive mining operations within small island territories, effectively transforming Indonesia’s environmental law landscape from an exploitative framework into a highly progressive, strongly binding, and sovereign environmental ecocracy system.